Influence of chitosan coatings with citric essential oil on the shelf-life of minimally processed mango (Mangifera indica L.) - Fabián Rico Rodríguez; Carolina Gutiérrez Cortés; Consuelo Díaz Moreno (Revista Facultad Nacional de Agronomía Medellín, 2015)
Demand for minimally processed fruits have increased due to their nutritional value and an increasing change in consumption habits. Physicochemical, microbiological, structural and sensory changes were determined in minimally processed mangoes (MPM) with chitosan (CH) edible coatings and lemon and orange essential oils (EOL). The MPM was first dipped in citric acid and a texturizing solution and then dipped in CH and lemon or orange EOL coatings. Weight loss, sensory acceptance, total soluble solids, total acidity, ascorbic acid, color changes, firmness and elasticity, and microbiological changes were quantified for 11 days of refrigerated storage. The CH and lemon EOL coating had more acceptance than the other treatments. No differences were found (p>0.05) for weight loss, total acidity, ascorbic acid, firmness or elasticity. There was a high amount of total phenols due to the EOL composition, as well as a high antioxidant capacity in the early days of storage. This characteristic decreased in the final days of the study. There was a decrease in the microbial charge for the lemon EOL treatment, as compared to the other samples. The CH and lemon EOL coating helped to maintain the shelf-life of the MPM for 11 days of storage without affecting the sensory acceptance. The CH and Orange EOL coating did not have an effect on the MPM physicochemical attributes; however, the sensory acceptance was negatively affected with off-flavors conferred to the MPM.